A VIEW ON THE EXPLORATION OF WASTE SERVICES FOR HEALTH COURSES OF HEALTH IN A UNIVERSITY COMMUNITY IN SOUTH BRAZIL - Muller, Adriani Maria; Silveira, Djalma Dias da; Nara, Elpidio Oscar Benitez; Kipper, Liane Mahlmann; Moraes, Jorge André Ribas (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This research aims a management system Waste Health Services - RSS - courses for health care from a community college, based on guidance provided by the Brazilian legislation linked to the health sector, the Environmental Management System, established by ISO 14001, and application of two questionnaires: one for collecting data from the students and one for faculty and staff. The research was exploratory and descriptive approaches used to integrate qualitative and quantitative analysis. It was found that 94% of students are unaware of the legislation concerning RSS and that 82% of teachers and officials do not know the destination of the waste. Other survey results demonstrated the need for more extensive and consistent information regarding RSS, generated in practical classes and community service. The knowledge of both the students and the faculty and staff, is focused and specific to each situation, there is a gap in the legislation and management of RSS. After the results were compiled systematic suggestions about Waste Management of Health Services, generated in teaching, which is a set of actions aiming at the quality and efficiency of academic practices, emphasizing environmental education.